Monitoring blood potassium concentration in hemodialysis patients by quantifying T-wave morphology dynamics - Flavio Palmieri (Nature Portfolio, 2021)
Abstract We investigated the ability of time-warping-based ECG-derived markers of T-wave morphology changes in time ( $$d_{w}$$ d w ) and amplitude ( $$d_a$$ d a ), as well as their non-linear components ( $${d_w^{NL}}$$ d w NL and $${d_a^{NL}}$$ d a NL ), and the heart rate corrected counterpart ( $$d_{w,c}$$ d w , c ), to monitor potassium concentration ( $$[K^{+}]$$ [ K + ] ) changes ( $$Δ [K^+]$$ Δ [ K + ] ) in end-stage renal disease (ESRD) patients undergoing hemodialysis (HD). We compared the performance of the proposed time-warping markers, together with other previously proposed $$[K^{+}]$$ [ K + ] markers, such as T-wave width ( $$T_w$$ T w ) and T-wave slope-to-amplitude ratio ( $$T_{S/A}$$ T S / A ), when computed from standard ECG leads as well as from principal component analysis (PCA)-based leads. 48-hour ECG recordings and a set of hourly-collected blood samples from 29 ESRD-HD patients were acquired. Values of $$d_w$$ d w , $$d_a$$ d a , $${d_w^{NL}}$$ d w NL , $${d_a^{NL}}$$ d a NL and $$d_{w,c}$$ d w , c were calculated by comparing the morphology of the mean warped T-waves (MWTWs) derived at each hour along the HD with that from a reference MWTW, measured at the end of the HD. From the same MWTWs $$T_w$$ T w and $$T_{S/A}$$ T S / A were also extracted. Similarly, $$Δ [K^+]$$ Δ [ K + ] was calculated as the difference between the $$[K^{+}]$$ [ K + ] values at each hour and the $$[K^{+}]$$ [ K + ] reference level at the end of the HD session. We found that $$d_{w}$$ d w and $$d_{w,c}$$ d w , c showed higher correlation coefficients with $$Δ [K^+]$$ Δ [ K + ] than $$T_{S/A}$$ T S / A —Spearman’s ( $$ρ$$ ρ ) and Pearson’s (r)—and $$T_w$$ T w —Spearman’s ( $$ρ$$ ρ )—in both SL and PCA approaches being the intra-patient median $$ρ \ge 0.82$$ ρ ≥ 0.82 and $$r \ge 0.87$$ r ≥ 0.87 in SL and $$ρ \ge 0.82$$ ρ ≥ 0.82 and $$r \ge 0.89$$ r ≥ 0.89 in PCA respectively. Our findings would point at $$d_{w}$$ d w and $$d_{w,c}$$ d w , c as the most suitable surrogate of $$Δ [K^+]$$ Δ [ K + ] , suggesting that they could be potentially useful for non-invasive monitoring of ESRD-HD patients in hospital, as well as in ambulatory settings. Therefore, the tracking of T-wave morphology variations by means of time-warping analysis could improve continuous and remote $$[K^{+}]$$ [ K + ] monitoring of ESRD-HD patients and flagging risk of $$[K^{+}]$$ [ K + ] -related cardiovascular events.